Right on target: Is public disclosure of non‐GAAP earnings associated with M&A efficiency? - Chen, Ciao‐Wei; Heflin, Frank; Ryu, Patrick W.; Wang, Jasmine (Contemporary Accounting Research, 2025)
Abstract We examine the association between target firms' public non‐GAAP earnings disclosures and merger and acquisition (M&A) efficiency. This research question is important, given the widespread use of non‐GAAP metrics in M&A valuation and lack of evidence regarding the real effects of non‐GAAP disclosure. Public non‐GAAP disclosure can enhance bidders' ability to assess a target's core earnings and potential synergy, especially in the earlier stages of due diligence, and enable bidders to make better M&A decisions. We find that target firms' non‐GAAP disclosures are associated with greater M&A efficiency, greater synergies, and lower likelihood of post‐acquisition goodwill impairment. We also find some evidence that target firms' non‐GAAP disclosures are positively related to post‐acquisition operating performance. Further, we find modest evidence that the positive relation between non‐GAAP disclosures and M&A efficiency is stronger (1) for targets that are more difficult to value, (2) for targets with weaker information environments, and (3) when targets' non‐GAAP numbers are of higher quality. Overall, our evidence suggests that non‐GAAP disclosures help facilitate efficient resource allocation in M&As and are associated with real effects on corporate investment. Our evidence is potentially relevant to regulators' concerns about the usefulness of non‐GAAP metrics.